2012
DOI: 10.1007/s10753-012-9556-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Mechanism of 10-Hydroxy-trans-2-decenoic Acid (Royal Jelly Acid) Against Lipopolysaccharide- and Interferon-β-Induced Nitric Oxide Production

Abstract: Royal jelly acid, 10-hydroxy-trans-2-decenoic acid (10H2DA), is a major lipid component of royal jelly, which is the exclusive diet of queen honeybees. Previously, we showed partial inhibition of lipopolysaccharide (LPS)-induced NF-κB activation by 10H2DA. In this study, the ability of 10H2DA to inhibit LPS-induced nitric oxide (NO) production was investigated. LPS-induced NO production and inducible NO synthase (iNOS) gene transcription were inhibited by 10H2DA. LPS-stimulated interferon (IFN)-β production, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 24 publications
6
26
0
Order By: Relevance
“…Previous research has demonstrated that 10-H2DA could inhibit NF- κ B activation via suppressing NO production and I κ B- ζ mRNA expression and transcription stimulated by LPS and IFN- β . Also, immunoblotting revealed that 10-H2DA did not inhibit LPS-induced IKK- α phosphorylation and I κ B α degradation [30]. In our study, 10-H2DA showed modest attenuating effects on I κ B α and enhanced the phosphorylation of p65, suggesting that 10-H2DA regulated LPS stimulation through more than one single pathway.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Previous research has demonstrated that 10-H2DA could inhibit NF- κ B activation via suppressing NO production and I κ B- ζ mRNA expression and transcription stimulated by LPS and IFN- β . Also, immunoblotting revealed that 10-H2DA did not inhibit LPS-induced IKK- α phosphorylation and I κ B α degradation [30]. In our study, 10-H2DA showed modest attenuating effects on I κ B α and enhanced the phosphorylation of p65, suggesting that 10-H2DA regulated LPS stimulation through more than one single pathway.…”
Section: Discussionmentioning
confidence: 49%
“…Previous studies have reported that 10-H2DA inhibits lipopolysaccharide- (LPS-) induced IL-6 production in a dose-dependent manner [30] and 10-H2DA inhibits LPS and IFN- β induced NO production via inhibition of NF- κ B [31]. Additionally, 10-HDAA could also inhibit LPS-induced NO production by inhibiting the translation of IRF-1 [32].…”
Section: Introductionmentioning
confidence: 99%
“…38 In line with the present research, Sugiyama et al reported RJ administration to inhibit nitrite oxide production. 39 The results of the present study suggested that RJ administration in both studied doses might have a positive effect on morphine-induced toxicity, as an oxidative stress, in the neurons of the prefrontal cortex; these effects are not dose-dependent concerning RJ.…”
Section: Discussionsupporting
confidence: 44%
“…Various immunomodulatory activities have been reported for 10-HDA, including reduced T cell proliferation, inhibition of interleukin-12 production by spleen dendritic cells, and block of LPS- and IFN-β-induced NO production in macrophages (Gasic et al, 2007; Sugiyama et al, 2013). In another study, a biphasic behavior of 10-HDA on human monocyte-derived dendritic cells has been found, resulting in Th1 response stimulation and Th2 downregulation at 50 μM, and repression of both Th1 and Th2 at 500 μM (Mihajlovic et al, 2013).…”
Section: Royal Jellymentioning
confidence: 99%